Konflik dalam Pemerintahan Nagari: Penelitian di Nagari Padang Sibusuk Kabupaten Sawahlunto Sijunjung Sumatera Barat - Dewi, Susi Fitria (Jurnal Demokrasi, 2006)
There is two kind of conflict when system governance of nagari gone into effect. The first, internal conflict in the form of conflict that happened among Wali Nagari with all Ninik Mamak. Wali Nagari with BPAN institute. The second, external conflict in the form of conflict among Padang Sibusuk nagari elite with Kampung Baru countryside elite. This External conflict is caused by desire of Kampung Baru which supported by sub-province party to cut loose from Padang Sibusuk nagari to become nagari alone. This desire get about ossifying from Padang Sibusuk nagari as nagari come from caused by binding of custom agreement and ownership of Padang Sibusuk society customary tanah ulayat in Kampung Baru region. To overcome this problem hence Padang Sibusuk elite raise letter of claim to Regent and DPRD Sawahlunto Sijunjung, inviting Kampung Baru elite to negotiate at rumah gadang and otherwise succeed also, wali nagari with his formed asistensi team of PTUN UU Perdakab Sawahlunto Sijunjung number 22/99 (now 32/2004 about governance of nagari), specially section 3 b sentence because assumed to support Kampung Baru to become a governance of nagari. Kata kunci:  Nagari, Political Conflict, Ninik Mamak, Alim Ulama,        Cerdik Pandai